Impact of Brand Loyalty on Consumer Repurchase Intention in Nepali Retail Markets - Awasthi, Hari Prasad (The Management Review, 2026)
The aim of the present research was to investigate the impact of "brand loyalty" on customer repurchase intention in the retail markets of Nepal, considering "customer satisfaction" as a mediating variable. Based on the theory of planned behavior and customer loyalty theory, the present study attempts to make contributions to the understanding of the impact of attitude based on brand loyalty on customer repurchase intention. Quantitative methods were used for the present research through an online survey among 385 consumers of retail markets. Partial Least Squares Structural Equation Modeling was used for the analysis of the collected data. Based on the findings of the present research, it was found that brand loyalty had an impact on customer satisfaction (β = 0.642, p < 0.001) and customer repurchase intention (β = 0.356, p < 0.001) multiple contributions are as follows: Besides, customer satisfaction was found to have an impact on customer repurchase intention (β = 0.481, p < 0.001).The model accounted for 41.2% of customer satisfaction and 58.6% of repurchase intention variance. The findings from the mediation analysis suggest that customer satisfaction is a partial mediator for brand loyalty and repurchase intention (β = 0.309, p < 0.001). The findings suggest that brand loyalty and customer satisfaction will lead to repurchase intention. This research contributes to the body of research on consumer behavior in developing nations. The findings have marketing implications for retail marketers operating in Nepal.